Strategies in Language Education to Improve Science Student Understanding during Practicum in Laboratory: Review and Computational Bibliometric Analysis - Siti Pupu Fauziah; Irman Suherman; Mega Febriani Sya; Martin Roestamy; Amirullah Abduh; Asep Bayu Dani Nandiyanto (Universitas Negeri Makassar, 2021)
The purpose of this study is to explain the development of language research in science learning which can improve students' understanding during practicums in the laboratory. This research also explores the factors that contribute to increasing student understanding and bibliometric analysis using the keywords